Development of instrumentation and simulation of regenerative motor-pump system for hydraulic hybrid vehicle / Mohamad Hilman Nordin - Mohamad Hilman , Nordin (2012)
The first decade of the 21st century had seen a growing and increasing concern on the lasting effects of human activities towards the environment. Issues such as global warming as well as the dwindling reserves of non-renewable sources of energy have forced the human race to look for the best replacement or alternative solutions, across all fields of industries. In the automotive industry, various researches are being conducted to produce sustainable transportation systems, which can be divided into the development of renewable source of energy as well as the improvement of energy efficiency. The improvement of energy efficiency has seen the growth of hybrid vehicles, which is proven to reduce the consumption of fuel and emission of pollutant. Regenerative braking is one of the systems applied in hybrid vehicles, where the energy used during braking is recovered and stored for future use. This study evaluates a Regenerative Motor-Pump System for the application of a Hydraulic Hybrid Vehicle (HHV). The instrumentation and control for the system was developed, where the design was tailored specifically for a truck. The Regenerative Motor Pump System was found to be able to recover 40% of the braking energy, resulting in 60% less energy required to move a HHV truck from stationary to 10 km/h, as compared to the total dependence to Internal Combustion Engine (ICE). Additionally, HHV and conventional vehicle simulation drivetrains were developed based on the experimental data obtained and tested on two different drive cycle tests. Firstly, a stop-and-go drive cycle show that the HHV truck was able to save up to 33% of energy compared to a conventional truck. Moreover, a comparison between conventional and a HHV truck using the New York Garbage Truck Cycle (NYGTC) shows a saving of energy up to 29.6%. The results obtained shows that there are significant benefits for the implementation of hydraulic-based regenerative braking systems, especially for vehicles with large mass undergoing multiple stop-and-go driving cycles.